Antimicrobial Resistance Profile of Different Clinical Isolates against Third-Generation Cephalosporins. (9th September 2018) - Gashe, Fanta; Mulisa, Eshetu; Mekonnen, Mekidim; Zeleke, Gemechu
Abstract : Background . Drug resistant microorganisms lead to an increase in morbidity and mortality as they boost the risk of inappropriate therapy. Hence, data on antimicrobial resistance help define the best possible treatment for individual patients. Therefore, this study aimed to screen the antimicrobial resistant profile of 3rd generation cephalosporin drugs in Jimma University Specialized Teaching Hospital. Methods . A hospital based prospective cross-sectional study was conducted in Jimma University Specialized Hospital (JUSH) from April to August 2016. The clinical samples such as wound swab, urine, sputum, and stool were collected from hospitalized patients. Then, bacterial species were isolated and identified as per the standard microbiological methods. Antimicrobial susceptibility tests were carried out using various antimicrobial discs by Kirby–Bauer disc diffusion method. Results . Totally, 248 bacterial isolates were obtained from 154 (62.1%) male and 94 (37.9%) female patients. Escherichia coli (25.4%) and Staphylococcus aureus (19.0 %) were the predominant organisms isolated from specimens. About 140 (56.5%) and 149 (60.1%) of the total bacterial isolates were found to be resistant to ceftriaxone and ceftazidime, respectively. The majority of Escherichia coli isolates 46 (73%) were resistant to ceftriaxone and 41 (65%) of them were resistant to ceftazidime. Staphylococcus aureus, which accounted 19% of the total bacterial isolates, showed 23.4% and 34% resistance to ceftriaxone and ceftazidime, respectively. Among the bacterial strains revealing resistant to ceftriazone and ceftazidime, about 109 (44%) and 108 (43.5%) of them were resistant to two, three, or four other drugs, respectively. Conclusion . Bacterial resistance towards third-generation cephalosporin (ceftriaxone and ceftazidime) is escalating as more than half of the isolated strains demonstrated resistance to these drugs. Moreover, these strains also revealed multidrug resistance mainly against clinically used drugs which could render therapy unsuccessful. Therefore, in clinical use appropriate medications should be selected based on the data obtained from antimicrobial susceptibility tests.